(untitled) (Bangladesh Journal of Child Health, 2017)
Background: Recurrent wheeze in infancy is a common clinical problem and one of the most important causes of health facility visits in Bangladesh. Recurrent wheeze is an important manifestation of bronchiolitis, pneumonia and asthma. Objectives: The study was conducted to identify the risk factors associated with recurrent wheeze in infancy. Methods: This case control study was conducted at Dhaka Shishu Hospital and Dhaka Medical College Hospital (DMCH) during August 2008- June 2009 including 50 infants (1- 12 months of age) with recurrent (3 or more) wheeze or wheeze persisting for more than one month during first year of life as study group and 50 children (12 months to 24 months of age) who had no wheeze during first year of life as control group Results: The study group comprised of 34 (68.0%) male and 16(32.0%) female infants and control group included 31(62.0%) male and 19 (38.0 %) female children. The mean age of study group was 9 months and that of the control group was 18 months. The median age of first attack of wheeze was 4 months. Twenty one (42.0%) infants in study group and 29 (58.0%) in control group were exclusively breastfed. On the other hand, 29 (58.0%) studied cases and 21(42.0%) controls were mixed fed (formula, cows milk, suji along with breast milk).The study children who were exclusively breastfed had lesser incidence of recurrent wheeze than those who were mixed fed but the difference was not significant (P> 0.05). There was past history of bronchiolitis in 45 (90.0%) cases of study group in comparison to only 3 (6.0%) cases of control group (p <0.05). Past history of pneumonia was present in 15 (30.0%) cases of study group compared to only 3 (6.0%) cases of control group (P <0.05). There was history of mothers asthma among 14 (28.0%) infants of study group versus only 1 (2.0%) mother of control group (P <0.05). There was history of fathers asthma in 8 (16.0%) cases of study group in comparison to none of control group (P<0.05). In this study we observed that 11 (22.0%) infants of study group had sibs suffering from wheeze compared to only 3 (6.0%) children of control group (<0.05). Sixteen (32.0%) infants of study group versus only 6 (12.0%) children of control group had atopic dermatitis and 33 (66.0%) cases of study group had suffered from allergic rhinitis whereas only 10 (20.0%) children had allergic rhinitis in control group (P<0.05). Atopic dermatitis and allergic rhinitis among study children were significantly associated with recurrent wheeze during infancy. Twenty (40.0%) study cases had exposure to tobacco smoke compared to 22 (44.0%) cases of control group. Exposure to tobacco smoke was not found to be associated with recurrent wheeze (P >0.05) Conclusion: The risk factors of recurrent wheeze in infancy identified in this study were past history of bronchiolitis , past history of pneumonia, asthma in parents (father and mother), wheeze in other sibs and atopic condition in children (atopic dermatitis, allergic rhinitis). Exclusively breastfed children had lesser incidence of recurrent wheeze than those who were mixed fed but the difference was not significant and exposure to tobacco smoke was not associated with recurrent wheeze in infancy in the present study. Bangladesh J Child Health 2017; VOL 41 (1) :9-14